Small‐Volume Plasmonic Microwell Array with 3D Hierarchical Nanomaterials for Plasmon‐Enhanced Fluorescence Immunoassay. Issue 1 (15th January 2021) - Choi, Wook; Lee, Won-Chul; Mun, ChaeWon; Kim, Sunho; Ansah, Iris Baffour; Kim, Shin-Hyun; Kim, Dong-Ho; Jung, Ho Sang; Park, Sung-Gyu
Abstract : Multiplex Detection In article number 2000015, Dong‐Ho Kim, Ho Sang Jung, Sung‐Gyu Park, and co‐workers present a small‐volume plasmonic microwell array with 3D hierarchical nanostructures for a plasmon‐enhanced fluorescence immunoassay. The 3D plasmonic microwell array exhibits a highly uniform and sensitive detection in a high‐throughput manner for a plasmon‐enhanced fluorescence‐based immunoassay of cardiac troponin I, a diagnostic biomarker for acute myocardial infarction.